2014
DOI: 10.3389/fimmu.2014.00336
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-Recognition Receptors and Gastric Cancer

Abstract: Chronic inflammation has been associated with an increased risk of several human malignancies, a classic example being gastric adenocarcinoma (GC). Development of GC is known to result from infection of the gastric mucosa by Helicobacter pylori, which initially induces acute inflammation and, in a subset of patients, progresses over time to chronic inflammation, gastric atrophy, intestinal metaplasia, dysplasia, and finally intestinal-type GC. Germ-line encoded receptors known as pattern-recognition receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 262 publications
(297 reference statements)
2
112
0
1
Order By: Relevance
“…There are some reports indicating that both TLR4 and TLR2 contribute in the early immune response against H. pylori, leading to the secretion of cytokines [31,32].…”
Section: Expression and Functions Of Tlr2mentioning
confidence: 98%
See 1 more Smart Citation
“…There are some reports indicating that both TLR4 and TLR2 contribute in the early immune response against H. pylori, leading to the secretion of cytokines [31,32].…”
Section: Expression and Functions Of Tlr2mentioning
confidence: 98%
“…nucleotide polymorphisms (SNPs) in the genes encoding TLR (such as TLR2 gene) showed an association with H. pylori-related gastrointestinal disorders [32,107]. The human TLR2 gene is placed on the long arm of chromosome 4 that possesses three exons including two 5ˊnon-coding exons and then after a third coding exon [108].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…31 The importance of the host's immune response in delineating the outcome of chronic H. pylori infection is reflected in the association of genetic polymorphisms with a higher risk for developing gastric cancer. These include IL-1b, 32 genes involved in Toll like receptor (TLR) and NOD-like receptor (NLR) signaling pathways 33,34 and the immunoregulatory transciption factor peroxisome proliferator activated receptor g (PPAR-g). 35 The relevance of these host factors will become apparent in the following sections discussing the current knowledge on innate and adaptive immune responses to H. pylori and how its virulence factors influence these processes.…”
Section: H Pylori and Its Human Host: An Intimate Relationshipmentioning
confidence: 99%
“…Studies concluded that polymorphism of IL17F was involved in suscepti bility to GC [87] . Current evidences support that TLRs are play roles in both recognition of H. pylori and gastric carcinogenesis, and polymorphisms in genes involved in the TLR signaling pathways modulate the risk of GC [88] . Additionally, peroxisome proliferatoractivated receptors may play roles in H. pylori-related gastric carcinogenesis [89] .…”
Section: Genetic Polymorphism Of H Pylori Hostsmentioning
confidence: 99%